The Potential Endophytic Bacteria Isolated from Rice (Oryza sativa) as Biofertilizer - Putriani Putriani; Lenni Fitri; Yulia Sari Ismail (Biosaintifika: Journal of Biology & Biology Education, 2019)
Endophytic bacteria are beneficial microorganisms that interact with host plants without causing any interference or damage to plants. This research aimed to obtain endophytic bacteria isolated from the root tissue of rice plants (Oryza sativa L.) which have potential to produce IAA hormones,, identify the endophytic bacteria in morphologically and physiologically, and analysis of the selected isolate 16S rRNA genes. Based on the results of this research, there  were six endophytic bacteria isolates obtained. They have high morphological diversity and differen ability producing IAA hormones. The highest concentration of IAA (425 ppm) was obtained  isolates from  EAP3. Isolate EAP3 also produce inhibit the growth of Xanthomonas oryzae with a 5.2 mm inhibition zone. Based on the biochemical test, EAP3 had 60% similarity with Enterobacter asburiae. Analysis of the 16S rRNA gene showed that EAP3 had the highest similarity with Enterobacter asburiae strain U4 by 99%. This research data is considered as new information about the potential of endophytic bacteria from the roots of rice plants (Oryza sativa L.) which is capable of producing IAA hormones and is able to inhibit pathogenic bacteria. This research provides information that can be used as a basis for developing endophytic bacteria as biological fertilizers.